The Implementation of Read, Asking, Paraphrase (RAP) Strategy in Improving the Learners’ Achievement in Reading Comprehension - Wahyuni, Resty; Cahya, Nurul (English Teaching and Linguistics Journal (ETLiJ), 2024)
This research discusses the Implementation of Read, Ask, Paraphrase (RAP) Strategy in Improving Students' Achievement in Reading Comprehension. This research was conducted at SMA TAMAN SISWA Medan in the odd semester 2023/2024 academic year. The number of samples was 44 students, the researcher method used was classroom action research method conducted in two cycles. This research was conducted to find out the students' improvement of students' achievement in reading comprehension by applying Read, Ask, Paraphrase (RAP) Strategy. The instruments used in this research are observation sheet and Reading Comprehension test which consists of 20 multiple choices. This study used descriptive quantitative data, quantitative data shows the average score of students from pre-test to post-test. In the Pre-test, the average score was 44.9. In the first cycle Post-test, the average student score was 65.8 and the second cycle Post-test, the average was 80.5, students who scored more than 75 in cycle I were 24 students and the percentage was 54.55%, students who scored more than 75 in cycle 2 were 42 students with a percentage of 95.45%. The results showed that the application of the Read, Ask, Put (RAP) strategy was successful because the success criteria had been achieved. The success criteria is 75% of students can pass the target score of 75 based on the Minimum Completeness Criteria (KKM). This means that the RAP Strategy can improve student achievement in reading comprehension